2021
DOI: 10.1021/acs.inorgchem.0c02579
|View full text |Cite
|
Sign up to set email alerts
|

Methane Generation from CO2 with a Molecular Rhenium Catalyst

Abstract: The atomic-level tunability of molecular structures is a compelling reason to develop homogeneous catalysts for challenging reactions such as the electrochemical reduction of carbon dioxide to valuable C1–C n products. Of particular interest is methane, the largest component of natural gas. Herein, we report a series of three isomeric rhenium tricarbonyl complexes coordinated by the asymmetric diimine ligands 2-(isoquinolin-1-yl)-4,5-dihydrooxazole (quin-1-oxa), 2-(quinolin-2-yl)-4,5-dihydrooxazole (quin-2-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…[23,24] In order to further understand the electrocatalytic CO 2 RR performance of complex 1 a broad variety of modulations of the bpy ligand and furthermore substitutions of bpy for comparable ligand platforms (e. g. pyNHC, pypz, pyiz) were investigated. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Among the large number of modified rhenium complexes and within the most studied class, the 4,4'substituted bpy rhenium complexes, the t Bu-derivative Re-(bpy-t Bu)(CO) 3 Cl (bpy-t Bu = 4,4'-di-tert-butyl-2,2'-bipyridine) is particularly noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] In order to further understand the electrocatalytic CO 2 RR performance of complex 1 a broad variety of modulations of the bpy ligand and furthermore substitutions of bpy for comparable ligand platforms (e. g. pyNHC, pypz, pyiz) were investigated. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Among the large number of modified rhenium complexes and within the most studied class, the 4,4'substituted bpy rhenium complexes, the t Bu-derivative Re-(bpy-t Bu)(CO) 3 Cl (bpy-t Bu = 4,4'-di-tert-butyl-2,2'-bipyridine) is particularly noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes based on a Re(I) tricarbonyl core with a dinitrogenated ligand (N,N such as 1,10-phenanthroline or 2,2 0 -bipyridine derivatives) in the equatorial position, and halogen or pyridine derivatives as ancillary ligands (X), have been extensively used for diverse applications, including solar cells, 1,2 catalysis, [3][4][5][6][7][8] and more recently, biological applications, [9][10][11][12][13][14][15][16][17] including staining of bacteria, yeasts (walled cells), and proteins separated by SDS-PAGE. 18,19 Photophysical attributes of fac-[Re(I)(CO) 3 (N,N)X] n complexes (where n is 0 or 1+) can be modulated by combining the (N,N) and X ligands.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, the Re 0 (bpy-R) − –CO 2 intermediates were added to the [Zn­(cyclam)] 2+ in two different binding modes of η 2 -OCO and η 1 -OCO . The local minima optimized geometry of the intermediate with the binding mode of η 2 -OCO rearranged to form the structure with η-OCO binding mode. The switching binding mode indicates that the η 1 -OCO binding is the stable mode in Re 0 (bpy-R) − −CO 2 –[Zn­(cyclam)] 2+ intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…Despite many efforts to reduce the CO 2 emission into the atmosphere, still the average temperature of the earth is increasing. The challenging issue associated with utilizing CO 2 is its thermodynamic stability and kinetic inertness due to the highest oxidation state of the carbon (+4) and the linear geometry of CO 2 with a short C–O bond length. Several studies have been reported to either reduce the existing CO 2 amount with an alternative energy source or converting CO 2 to a useful raw material such as carbon monoxide (CO) or CH 4 . …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation